Pemanfaatan Aplikasi Keuangan di Smartphone untuk Manajemen Keuangan Usaha Pada Kelompok PKK Kelurahan Rambung Barat - Fuzy Yustika Manik; Dewi Sartika Br. Ginting; Tetty Yuliaty (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
The purpose of this service is to provide training and assistance to PKK members to be able to manage finances and manage business finances. The method used is a social approach. Where the preparation stage is carried out by conducting surveys and observations to identify problems and analyze the situation and community needs. Then carried out the implementation stage with two main activities, namely training and mentoring. During the training, PKK members were given knowledge in financial management and practical financial management with applications. Assistance is provided when participants practice directly using the application. Based on the evaluation carried out, it is known that the results of this service have increased the knowledge of PKK members about financial management with an average posttest score of 70. Through the assistance carried out, each PKK member already has an account in one of the applications. financial management, and can be used for recording every transaction, debt to recording stock of goods that are still available